Fusion Dynamics of Low-Energy Heavy-Ion Collisions for Production of Superheavy Nuclei - Bao, Xiao Jun (Frontiers in Physics, 2020)
One of the major motivation of low energy heavy-ion collision is the synthesis of superheavy nuclei. Based on the following two main aspects, various theoretical and experimental research have been performed to study the fusion dynamical process of superheavy nuclei production. The first reason is to elucidate and analyze the synthesis mechanism of superheavy nuclei; the other is to search the favorable incident energy and the best combination of projectile and target to produce new superheavy elements and isotopes of superheavy elements.